2013
DOI: 10.1186/1477-7827-11-30
|View full text |Cite
|
Sign up to set email alerts
|

Effects of corticotrophin releasing hormone (CRH) on cell viability and differentiation in the human BeWo choriocarcinoma cell line: a potential syncytialisation inducer distinct from cyclic adenosine monophosphate (cAMP)

Abstract: BackgroundPlacental production of corticotrophin releasing hormone (CRH) rises exponentially as pregnancy progresses, and has been linked with the onset of normal and preterm labour. CRH is produced in syncytiotrophoblast cells and production is increased by glucocorticoids and cAMP. It remains unclear whether cAMP acts by inducing differentiation of cytotrophoblasts and/or through induction of syncytialisation. As CRH can stimulate cAMP pathways we have tested whether a feed-forward system may exist in placen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 39 publications
3
4
0
Order By: Relevance
“…8-Br-cAMP increased CRH mRNA abundance relative to vehicle at all time points (24 h, p = 0.0042; 48 h, p = 0.0066; 72 h, p = 0.0004; Figure 1 ), which confirmed previous findings of the stimulatory effects of 8-Br-cAMP on CRH gene expression in BeWo cells [ 28 ]. 5-AZA-dC treatment had no effect at 24 h and 48 h and reduced CRH mRNA abundance relative to vehicle at 72 h, effectively blocking the increase seen between 48 h and 72 h in vehicle-treated cells ( p = 0.0021, Figure 1 ).…”
Section: Resultssupporting
confidence: 89%
“…8-Br-cAMP increased CRH mRNA abundance relative to vehicle at all time points (24 h, p = 0.0042; 48 h, p = 0.0066; 72 h, p = 0.0004; Figure 1 ), which confirmed previous findings of the stimulatory effects of 8-Br-cAMP on CRH gene expression in BeWo cells [ 28 ]. 5-AZA-dC treatment had no effect at 24 h and 48 h and reduced CRH mRNA abundance relative to vehicle at 72 h, effectively blocking the increase seen between 48 h and 72 h in vehicle-treated cells ( p = 0.0021, Figure 1 ).…”
Section: Resultssupporting
confidence: 89%
“…CRHR, POMC and the ACTHR have also been detected in the placenta [76,77], where we recently demonstrated a sixfold Syncytin-1 induction of expression in human primary trophoblasts after 48 h of CRH treatment [50]. It was also shown that CRH resulted in the induction of CRHR1 and syncytialization, similar to cAMP alone [78]. Our immunofluorescence and IHC experiments taken together with our primary PA cell culture further corroborates a possible and positive connection between ERV gene expression and cAMP signalling.…”
Section: Discussionsupporting
confidence: 83%
“…Raw CT values were processed using the DCT method relative to the geometric mean of two reference genes, ACTB and GAPDH. These reference genes have been widely utilized in other studies of choriocarcinoma cell line mRNA expression levels (Lee et al, 2004;Chiu et al, 2007;Li et al, 2008;Masumoto et al, 2011;Mparmpakas et al, 2012;Chen et al, 2013). DCT values generated relative to ACTB and GAPDH were highly correlated in all assays included in this study (Supplementary data, Fig.…”
Section: Quantitative Real-time Pcrmentioning
confidence: 98%